2019
DOI: 10.1097/md.0000000000015279
|View full text |Cite
|
Sign up to set email alerts
|

Transfusions and cost-benefit of oral versus intravenous tranexamic acid in primary total hip arthroplasty

Abstract: Background:The purpose of this study was to assess the cost benefit and transfusions of oral and IV tranexamic acid (TXA) in primary total hip arthroplasty (THA).Methods:PubMed, Embase, Web of Science, and the Cochrane Library were systematically searched for randomized controlled trials (RCTs) comparing oral and IV TXA in primary THA. Primary outcomes were total blood loss, maximum hemoglobin drop, transfusion requirements, and cost benefit. Secondary outcomes were length of stay, deep venous thrombosis (DVT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
(73 reference statements)
0
9
0
1
Order By: Relevance
“…Treatment with tranexamic acid has been used to reduce blood loss and transfusion rates in orthopedic surgery. [28][29][30] However, our protocol focused not only on blood conservation management but also on reproduction by inducing erythropoiesis. 2,6) Despite the PBM protocol, in the fracture patients, the hemoglobin level declined until the postoperative day 3, which was followed by a gradual increase.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with tranexamic acid has been used to reduce blood loss and transfusion rates in orthopedic surgery. [28][29][30] However, our protocol focused not only on blood conservation management but also on reproduction by inducing erythropoiesis. 2,6) Despite the PBM protocol, in the fracture patients, the hemoglobin level declined until the postoperative day 3, which was followed by a gradual increase.…”
Section: Discussionmentioning
confidence: 99%
“…These savings are largely associated with a reduction in blood transfusions and their associated costs. 8,13,14 Reduced length of stay and improvements in early functional outcomes have also been reported. 15,16 A cost analysis was undertaken in conjunction with this trial.…”
Section: Introductionmentioning
confidence: 93%
“…[2][3][4][5][6][7] Highrisk patients such as those with previous venous thromboembolism (VTE), myocardial infarction (MI), and cerebrovascular accidents (CVAs) have been excluded from orthopaedic trials to date. 8 Various dosing regimens have also been described, with support in the literature for extending oral or intravenous (IV doses of TXA to reduce blood loss further and potentially improve patient outcomes. 9,10 The most effective regime, however, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that perioperative intravenous infusion of TXA can reduce total blood loss, intraoperative blood loss, and blood transfusion rate during joint replacement surgery, and that it does not increase the risk of venous thrombosis. Its safety has been recognized by clinical experts [4][5][6][7]. fracture surgery.…”
Section: Introductionmentioning
confidence: 99%